The Role of Prosocialness and Trust in the Consumption of Water as a Limited Resource - Cuadrado, Esther; Tabernero, Carmen; García, Rocío; Luque, Bárbara; Seibert, Jan (Frontiers in Psychology, 2017)
This research analyzes the role of prosocialness and trust in the use of water as a limited resource under situations of competition or cooperation. For this purpose, 107 participants played the role of farmers and made decisions about irrigating their fields in the web-based multiplayer game Irrigania. Before the simulation exercise, participants’ prosocialness and trust levels were evaluated and they were randomly assigned to an experimental condition (competition or cooperation). Repeated measures analysis, using the 10 fields and the experimental conditions as factors, showed that, in the cooperation condition, farmers and their villages used a less selfish strategy to cultivate their fields, which produced greater benefits. Under competition, benefits to farmers and their villages were reduced over time. Mediational analysis shows that the selfish irrigation strategy fully mediated the relationship between prosocialness and accumulated profits; prosocial individuals choose less selfish irrigation strategies and, in turn, accumulated more benefit. Moreover, moderation analysis shows that trust moderated the link between prosocialness and water use strategy by strengthening the negative effect of prosocialness on selection of selfish strategies. The implications of these results highlight the importance of promoting the necessary trust to develop prosocial strategies in collectives; therefore, the efficacy of interventions, such as the creation of cooperative educational contexts or organization of collective actions with groups affected by water scarcity, are discussed.